Upper Gastrointestinal Bleeding in Children: A Tertiary United Kingdom Children's Hospital Experience - Omar Nasher; David Devadason; Richard J. Stewart (MDPI AG, 2017)
The aim of this study was to review the aetiology, presentation and management of these patients with upper gastrointestinal bleeding (UGIB) at a tertiary children's unit in the United Kingdom. This was a retrospective single-institution study on children (<16 years) who presented with acute UGIB over a period of 5 years using known International Classification of Diseases (ICD) codes. A total of 32 children (17 males, 15 females) were identified with a total median age at presentation of 5.5 years. The majority (24/32) of patients presented as an emergency. A total of 19/32 presented with isolated haematemesis, 8/32 with isolated melaena and 5/32 with a combination of melaena and haematemesis. On admission, the mean haemoglobin of patients who presented with isolated haematemesis was 11 g/dL, those with isolated melaena 9.3 g/dL and those with a combination 7.8 g/dL. Blood transfusion was required in 3/19 with haematemesis and 3/5 with haematemesis and melaena. A total of 19/32 underwent upper gastrointestinal endoscopy. Endoscopic findings were oesophageal varices (5/19) of which 4 required banding; bleeding gastric ulcer (1/19) requiring clips, haemospray and adrenaline; gastric vascular malformation (1/19) treated with Argon plasma coagulation therapy; duodenal ulcer (3/19) which required surgery in two cases; oesophagitis (5/19); and gastritis +/− duodenitis (3/19). A total of 13/32 patients did not undergo endoscopy and the presumed aetiology was a Mallory-Weiss tear (4/13); ingestion of foreign body (2/13); gastritis (3/13); viral illness (1/13); unknown (2/13). While UGIB is uncommon in children, the morbidity associated with it is very significant. Melaena, dropping haemoglobin, and requirement for a blood transfusion appear to be significant markers of an underlying cause of UGIB that requires therapeutic intervention. A multi-disciplinary team comprising gastroenterologists and surgeons is essential.